Peran Jamaah Yasinan sebagai Pusat Pemberdayaan Masyarakat (Studi di Dusun Brajan Prayungan Sawoo Ponorogo) - Mulyono, Mulyono (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2009)
Initially Yasinan represent activity of religious ritual which later; then round into local organization so that function as one of the strength of religious social. With formed its of organization, hence Jamaah Yasinan have role which progressively wide of among others as medium missionize and effective religious social activity means progressively. That thing is as conducted by fficial member of Jamaah Yasinan Al-Hidayah in Orchard of Brajan Countryside of Prayungan District Of Sawoo Ponorogo East Java. Since early fficial member of this Jamaah realize that from a number of media and method missionize performed within range of time 24 year ( l985-2009) hence activity of Yasinan assessed most successful in sending society transformation of abangan become religious society. Hence pursuant to experience, official member of Al-Hidayah intend to develop role of Jamaah Yasinan become as activity of religious ritual, religious social and at the same time center impowerment of society in global era. As for effort conducted development the official member of Al-Hidayah in powered and improve role of Jamaah Yasinan as Impowerment Society Center for example passing: (1) organizational management / jamaah; (2) construction items; (3) fnancing; (4) facilities and basic facilities; (5) program coordination and harmonization; (6) Jamaah Yasinan with notary akte by the name of: Social Institute and Mission of Al-Hidayah brief by Lemsosda; (7) improving cooperation; and (8) construction by sustainable.